Dysbiosis of the gut microbiota as a susceptibility factor for Kawasaki disease - Teramoto, Yoshiki; Akagawa, Shohei; Hori, Shin-ichiro; Tsuji, Shoji; Higasa, Koichiro; Kaneko, Kazunari (Frontiers in Immunology, 2023)
Gut microbial imbalance (dysbiosis) has been reported in patients with acute Kawasaki disease (KD). However, no studies have analyzed the gut microbiota while focusing on susceptibility to KD. This study aimed to evaluate whether dysbiosis elevates susceptibility to KD by assessing children with a history of KD. Fecal DNA was extracted from 26 children with a history of KD approximately 1 year prior (KD group, 12 boys; median age, 32 months; mean time from onset, 11 months) and 57 age-matched healthy controls (HC group, 35 boys; median age, 36 months). 16S rRNA gene analysis was conducted with the Illumina Miseq instrument. Sequence reads were analyzed using QIIME2. For alpha diversity, Faith’s phylogenetic diversity was significantly higher in the KD group. Regarding beta diversity, the two groups formed significantly different clusters based on Bray–Curtis dissimilarity. Comparing microbial composition at the genus level, the KD and HC groups were significantly different in the abundance of two genera with abundance over 1% after Benjamini–Hochberg false discovery rate correction for multiple comparisons. Compared with the HC group, the KD group had higher relative abundance of Ruminococcus gnavus group and lower relative abundance of Blautia. Ruminococcus gnavus group reportedly includes pro-inflammatory bacteria. In contrast, Blautia suppresses inflammation via butyrate production. In the predictive functional analysis, the proportion of gut microbiota involved in several pathways was lower in the KD group. Therefore, dysbiosis characterized by distinct microbial diversity and decreased abundance of Blautia in parallel with increased abundance of Ruminococcus gnavus group might be a susceptibility factor for KD.